A Mid- to Long-Term Follow-Up Experience with a Specific Metal-on-Metal Total Hip Arthroplasty Design - Carulli, Christian; Sani, Giacomo; Matassi, Fabrizio; Civinini, Roberto; Innocenti, Massimo (Joints, 2019)
Purrpose Metal-on-metal (MoM) total hip arthroplasty (THA) has been a subject of recent discussion and concern due to the early failures caused by local and systemic adverse reactions related to specific designs. The aim of this study is to analyze the outcomes and survival rates of a single brand of MoM implants implanted in a consecutive series of patients at a single institution.Methods Between 2007 and 2012, 116 (118 hips) patients were evaluated at a mean follow-up of 6.6 years after primary THA. The diagnosis leading to surgery was osteoarthritis (80 patients) and proximal femoral fracture (36 patients). A single design of THA was implanted. All patients were evaluated before surgery and postoperatively at 1, 3, 6, and 12 months by clinical scores and radiographic studies. The data analysis was made using Student's t-test.Results The minimum follow-up was of 4 years, with a mean follow-up of 6.6 years. Two aseptic loosenings of the acetabular component were recorded (one per group), which were not associated with local or systemic complications related to metal ion release. Both were revised by an isolated acetabular cup substitution with metal-on-polyethylene couplings. Nonprogressive radiolucency lines < 2 mm in zone 2 were observed in other six patients around the acetabular component without clinical manifestation (four in the arthritis group and two in the fracture group). Postoperative Harris Hip Score and SF-36 (36-Item Short Form Survey) score improved in both groups.Conclusion Despite several MoM implants showing early complications and failures, a specific MoM design may be associated with good clinical results at a mid- to long-term follow-up.Level of Evidence This is a therapeutic case series, Level 4 study.
Keywords: metal-on-metal total hip arthroplasty; total hip arthroplasty; metal ion release; hip arthritis; proximal femoral fractures